Determination of serum zinc concentration in normal healthy men & type II diabetes mellitus patients. - Kader Kamel, Nasreen (Tikrit Journal of Pharmaceutical Sciences, 2023)
Body zinc content is regulated by the homeostatic mechanism, which regulate zinc absorption and excretion depending on its body requirements. The function of cells and tissues enzymes is depend zinc content & over 70 human body enzymes with which zinc is associated. Pervious studies show that some trace elements like magnesium, zinc, manganese & selenium may play important role in action of insulin hormone, including activation of insulin receptor sites. The aim of the study is to determine the serum level of zinc in normal healthy men & diabetes mellitus type II patients. A cross sectional study was done in Tikrit teaching hospital from beginning of January to end of December 2010. The study conducted on 50 type 2 diabetic male patients was participated in the study. While, 30 normal healthy men age matched (aged 55 to 60 years) were included as a control. Serum zinc was measured for control healthy non diabetic subjects & diabetic type 2 patients. There were non significant differences regarding age. However there is significant increase in BMI of diabetic patients as compare with control men. Fasting serum glucose was significantly higher in DM patients as compare with control subjects. Moreover, there is significant reduction in serum zinc in diabetic patients (89.35 ± 19.23 µg/dl) as compare with normal health subjects (135 ± 35.18 µg/dl). In diabetic patients, there is significant negative correlation between fasting blood sugar & serum zinc (r= - 0.37). In present study conclude that there is a significant reduction in serum zinc in diabetic patients. The present study recommend that diabetic type II patients should be encourage to eat diet rich in zinc or take zinc supplement.